Diurnal bird raptors of Llanos de Moxos, Bolivia - Daniele, Gonzalo; Kacoliris, Federico Pablo; Berkunsky, Igor (Neotropical Biology and Conservation)
Raptor abundance has been poorly documented in the Neotropics. Here we describe the abundance and composition of the diurnal bird raptor community of Llanos de Moxos, one of the largest and less studied Neotropical savannah. During four consecutive breeding seasons (i.e., August 2007 to February 2008, August 2008 to January 2009, August 2009 to January 2010, and August 2010 to January 2011), we monitored 11 transects and 30 points, searching for raptors’ activity. We detected 29 diurnal bird raptor species in the region, which represented almost half of diurnal bird raptor species of Bolivia. As expected, scavengers and generalists were most frequent and abundant diurnal bird raptors. The Llanos de Moxos shared 83% of raptor species with Venezuelan Llanos and 67% with Chaco wetlands. The Llanos de Moxos is an important migratory and conservation region for some species as Swainson’s hawk, Chaco eagle, osprey and peregrine falcon. The lack of effective protected areas in the region is concerning, and, thus, the establishment of such areas should be a conservation priority. A abundância de aves de rapina tem sido pouco documentada na região Neotropical. No presente trabalho, descrevem-se a abundância e a composição da comunidade diurna de aves de rapina de Llanos de Moxos, uma das maiores e menos estudadas savanas neotropicais. Durante quatro períodos de reprodução consecutivos (agosto de 2007 a fevereiro de 2008, agosto de 2008 a janeiro de 2009, agosto de 2009 a janeiro de 2010 e agosto de 2010 a janeiro de 2011), foram monitorados 11 transectos e 30 pontos, buscando atividades de aves de rapina. Detectamos 29 espécies de aves de rapina diurnas na região, que representaram quase metade das espécies dessas aves diurnas da Bolívia. Como esperado, os detritívoros e generalistas foram as aves de rapina diurnas mais frequentes e abundantes. Os Llanos de Moxos compartilharam 83% de espécies de aves de rapina com Llanos venezuelanos e 67% com áreas úmidas de Chaco. Os Llanos de Moxos representam uma importante região ...